THE EFFECT OF USING THE QR CODE ABSENCE INFORMATION SYSTEM ON STUDENT DISCIPLINE - Lisna Yanti; Vandan Wiliyanti; Yetri Hasan; Yosep Aspat Alamsyah (Universitas Islam Negeri (UIN) Sumatera Utara, 2026)
This research is intended to assess how the use of an information system influences QR Code–based attendance on student discipline at SMP Negeri 2 Bandar Lampung. The study employed applies a quantitative framework with a causal associative design, and the population of the research comprises consisted of 1,074 students, with a sample of 292 respondents determined using the Slovin formula at a 5% margin of error and using a robability sampling approach, respondnets were chosen through simple random sampling. Data collection employed a likert scale questionnaire with scores from 1 to 4, and analysis was conducted using the SEM-PLS technique supported by SmartPLS version 4. It can be inferred from the findings that QR Code–based attendance has a positive and significant effect on student discipline, with an R-square value of 0.441. The hypothesis testing results show a t-statistic value of 18.459 and a p-value of 0.000. These findings demonstrate that an integrated and real-time attendance system can improve punctuality, reduce fraudulent practices, and foster students’ responsibility toward their academic obligations. This study highlights that the utilization of information technology in attendance management represents an effective strategy for enhancing student discipline